Polyaniline composite membranes synthesis in presence of various acid dopants for pressure filtration - Rosiah Rohani,; Izzati Izni Yusoff,; Farah Adlyna Mey Efdi,; Mohd Usman Mohd Junaidi,; Qaiser, Asif Ali (Penerbit Universiti Kebangsaan Malaysia, 2017)
Polyaniline is a conductive polymer that is recently used as a material in producing a pressure filtration membrane. Polyaniline can be doped in various acids as dopants of different sizes and shapes to modify its inherent properties to produce membrane with high flux and rejection. This work is aimed to fabricate polyaniline composite membrane in presence of different acids as dopants namely hydrochloric acid, maleic acid, poly(methyl vinylether) acid (PMVEA) and polyacrylic acid (PAA). This polyaniline was coated onto microporous polyvinylidene fluoride (PVDF) support by using a specially fabricated two compartment cell. The field emission scanning electron microscope (FESEM) results show that the morphology of the coated polyaniline on PVDF membrane support is in globular shapes, which elongates at different sizes depending to the acid used. From the thermal analysis, the melting point of polyaniline coated PVDF membrane remains at 260°C, similar as obtained in the pristine microporous PVDF indicating no thermal change upon polyaniline coating. From all membranes prepared, the doped polyaniline membrane possessed a good conductivity value except for polyaniline-PMVEA membrane, which has the lowest value. In terms of the membrane filtration performance, which was measured based on the flux of pure water and polyethylene glycol (PEG) rejection, polyaniline-PMVEA membrane has a high flux and the highest PEG rejection. This result indicates that the conductivity does not influence much on the membrane filtration performance, but rather due to the physical coating itself. Different acid dopants present during polyaniline coating will lead to different filtration performance.